2000
DOI: 10.1101/gr.10.7.991
|View full text |Cite
|
Sign up to set email alerts
|

From Complete Genomes to Measures of Substitution Rate Variability Within and Between Proteins

Abstract: Accumulation of complete genome sequences of diverse organisms creates new possibilities for evolutionary inferences from whole-genome comparisons. In the present study, we analyze the distributions of substitution rates among proteins encoded in 19 complete genomes (the interprotein rate distribution). To estimate these rates, it is necessary to employ another fundamental distribution, that of the substitution rates among sites in proteins (the intraprotein distribution). Using two independent approaches, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 45 publications
8
76
0
Order By: Relevance
“…This opens the possibility that the complex is performing some critical role within the cell and that its functionality requires both CDC33 and either one of the two paralogs. We note that analysis and interpretation of protein evolutionary rates in the context of our assembled set of complexes may provide another interesting research direction (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…This opens the possibility that the complex is performing some critical role within the cell and that its functionality requires both CDC33 and either one of the two paralogs. We note that analysis and interpretation of protein evolutionary rates in the context of our assembled set of complexes may provide another interesting research direction (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…At the genome scale, a recent analysis of the mitochondrial genomes of mammalian species has revealed that the global molecular clock was clearly violated for both the amino acid and nucleotide data (Yoder and Yang 2000). Another study among distant species suggests that a generalized version of the molecular clock hypothesis may be valid on the genome scale (Grishin et al 2000). These conflicting results emphasize the importance of the evolutionary intervals considered, because a comparison between distant groups of species may omit the subtle but significant differences existing between closely related species.…”
Section: Testing the Molecular Clock Hypothesis At The Genome Scalementioning
confidence: 99%
“…Previous analyses have shown that the distributions of evolutionary distances (or simply percent sequence identity) between pairs of orthologous proteins had the same shape, up to a scaling factor, for a wide range of evolutionary distances (Grishin et al 2000). Therefore, parameters of such distributions, in particular the median, can be employed to calculate evolutionary distances between species and to construct neighbor-joining or leastsquares trees (Wolf et al 2001(Wolf et al , 2002.…”
Section: Trees Built Using the Median Similarity Between Orthologs Asmentioning
confidence: 99%